Interdisciplinarity and multidisciplinarity of the medical profession. Opportunity or threat? - Sytnik-Czetwertyński, Janusz; Augustynowicz, Anna; Skowron, Adam; Waszkiewicz, Michał; Grudziąż-Sękowska, Justyna; Hajdukiewicz, Dariusz; Kobuszewski, Bartosz; Janiszewska, Lidia; Wrześniewska-Wal, Iwona (Journal of Education, Health and Sport, 2019)
This article aims to describe the actual scope of requirements for physicians and analyse it as an opportunity for, or threat to, the development of the profession. The article will be subdivided into two parts. In the first, concerning the interdisciplinarity of the medical profession, we shall provide constructive criticism of the specialisation system within the medical profession. This part will be subdivided into two segments: the first will list the opportunities for physicians which result from often far-reaching specialisation, while the second will enumerate the threats. The second part, dealing with the multidisciplinarity of the medical profession will define the scope of actual competences required from physicians so as to judge whether such a large amount of additional knowledge is helpful for physicians in fulfilling their professional requirements, or if it overwhelms them.